Craniofacial Trauma Due to Stone-pelting – Patterns of Injury and Management. Issue 4 (June 2021) - Arya, Saurabh; Jose, Anson; Rangan, N. Mohan
Abstract : Aim: The aims of the study were to elucidate the pattern of stone-pelting induced cranio-facial injuries and to document soft and hard tissue injuries, their management, and complications. Methods: A retrospective descriptive study was conducted using a sample of patients reporting to our department in the years 2015 to 2020. Cranio-facial injuries were assessed for soft and hard tissue injuries, including tissue loss, and corresponding management. Follow up ranged from 18 ± 6 months. & A standardized surgical regime was followed for patient management, which included primary survey, debridement of wounds, and routine primary repair of soft tissue. Bony defect reconstruction was performed by open reduction and internal fixation. Cranial bone was used as split calvarial graft in postcraniectomy cranioplasty procedures, which were performed after 6 months. Local flaps were used for the reconstruction of soft tissue defects. Results: Being a military hospital, majority of cases fell in the 20 to 30 age group with a male preponderance. The etiology in all cases was stone-pelting. Among cranio-facial injuries, cranial vault injuries and mid-face injuries (71%) were most prevalent, mandibular fractures (24%) and remaining were soft tissue injuries (5%). & Frontal & parietal bone injuries were seen in 23.6% cases (n = 9) and orbito-zygomatic complex injuries were seen in (36.8%) cases (n = 14). Isolated blow-out fractures were seen in 4 patients of our series. 52.6% of patients of our series suffered associated soft tissue injuries to the head, face, and neck region. The most common cause of injury was due to the direct impact of stone hitting the mid-face/cranial vault and the most common pattern of injury was gross comminution of the skeleton. & 2 patients suffered ocular injuries that required management and 6 patients of our series who suffered head injuries to the cranium required a secondary cranioplasty procedure (n = 4) &The most commonly used technique for treatment was open reduction internal fixation, which was used in 89% of patients. Soft-tissue injuries overall occurred most frequently on the forehead, nose, lips, and chin which was managed by primary suturing. Conclusions: Cranial vault injuries & orbito-zygomatic complex fractures are most commonly seen in patients with stone-pelting injuries. Early management of such injuries improves outcomes in terms of function and restitution of preinjury skeleton structure. The most common patterns seen is gross comminution to the cranio-facial skeleton that can be treated with immediate primary wound repair after meticulous wound debridement and open reduction and internal fixation. Importance of stone-pelting as a cause of craniofacial injuries is highlighted as it leads to significant disruption of craniofacial skeleton. Abstract : Supplemental Digital Content is available in the text